Dendritic cell combination therapy reduces the toxicity of triptolide and ameliorates colitis in murine models - Quan Rao; Guang-chao Ma; Hao Wu; Meng Li; Wei Xu; Guo-jun Wang; Dong Wang; Cong-en Zhang; Zhi-jie Ma; Zhong-tao Zhang (Taylor & Francis Group, 2022)
Triptolide (TP) exerts a promising effect in the treatment of ulcerative colitis (UC). However, its toxicity seriously hinders its application in the clinic. Previous studies indicated that dendritic cells (DCs) are the main target through which TP exerts its immunoregulatory effect. Thus, we designed an approach to target DCs in vitro to avoid the direct exposure of organs to TP. Our results revealed that DCs pretreated with TP (DCTP) exerted satisfactory therapeutic effects in mice with colitis, resulting in improved colonic inflammation and alleviated local lesion damage. In addition, no obvious toxicity was observed. DCTP also reshaped the immune milieu by decreasing CD4+ T cell numbers and increasing regulatory T cell numbers in the spleen, mesenteric lymph nodes, peripheral blood and colon; these effects were further confirmed in vitro. Downregulation of CD80/86, ICAM-1, MHCI, TLR2/4, TNF-α, and IL-6 expression and upregulation of programmed cell death ligand 1 (PDL1) and IL-10 expression were observed, indicating that DCs were converted into tolerogenic DCs. In conclusion, DCTP can effectively reduce toxicity and alleviate colonic inflammation and local lesion damage in mice with colitis. The immune mechanism underlying the effects of DCTP included the conversion of DCs into tolerogenic DCs and the alteration of T cell differentiation to produce immunoinhibitory rather than immunostimulatory T cells.